Patterned Matrix Pertemuan 13. Matakuliah : Matrix Algebra for Statistics Tahun : 2009. Patterned. Matrices that have a particular pattern occur frequently in statistics. Such matrices are typically used as intermediary steps in proofs and in perturbation techniques.
Download Policy: Content on the Website is provided to you AS IS for your information and personal use and may not be sold / licensed / shared on other websites without getting consent from its author.While downloading, if for some reason you are not able to download a presentation, the publisher may have deleted the file from their server.
Matakuliah : Matrix Algebra for Statistics
Tahun : 2009
Matrices that have a particular pattern occur frequently in statistics. Such matrices are typically used as intermediary steps in proofs and in perturbation techniques.
Patterned matrices also occur in experimental designs and in certain variance matrices of random vectors
a) Identities that are useful, Assumed (that all inverses exist)
i) VA-1(A - UD-1V) = (D - VA-1U)D-1V,
ii) D-1V(A - UD-lV)-1 = (D - VA-1U)VA-1
b) Setting A = I, D = -I, and interchanging U and V in a) ii), we have that U(I + VU)-1= (I + UV)-LU
(c) If I + U is nonsingular,
(I + U)-1 = I - (I + U ) - W = I - U(I + U) -1
(d) U'A-1U(I + U'A-1U)-1= I - (I + U'A-1U)-1.
e) If A and B are n x n complex matrices, then
In+ AA' = (A + B)(In+ B*B)-1(A + B)*
+ In-AB*)(I, +BB*)-1(In -AB*)*
If A is nonsingular and the other matrices are conformable square or rectangular matrices (e.g., A is nxn, U is nxp , B is pxq, and V is qxn), then
(A + UBV)-1= A-1- (I + A-1UBV)-1A-1UBVA-1
=A-1- A-1(I + UBVA-1)-1UBVA-1
=A-1- A-1U(1 + BVA-1U)-1BVA-1
=A-1- A-1UB(1 + VA-1UB)-1VA-1
=A-l - A-1UBV(1 + A-1UBV)-1A-1
=A-1- A-1UBVA-1(I + UBVA-1)-1
Gentle [1998: 621 notes that in linear regression we often need inverses of various sums of matrices and gives the following additional identities for nonsingular A and B.
a) (A + BB')-lB = A-1B(I + B'A-1B) -1
b) (A-1+ B-l) -1= A(A + B) -1B.
c) A(A + B) -1B = B(A + B)-lA.
d) A-1+ B-1= A-l(A + B)B-1
We can also add, for nonsingular A + B,
e)A - A(A + B)-1A = B - B(A + B) -1B.